2008
DOI: 10.1158/0008-5472.can-08-0002
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Instability Caused by Loss of MutS Homologue 3 in Human Colorectal Cancer

Abstract: Microsatellite instability (MSI) is a hallmark of mismatch repair (MMR) deficiency. High levels of MSI at mononucleotide and dinucleotide repeats in colorectal cancer (CRC) are attributed to inactivation of the MMR genes, hMLH1 and hMSH2. CRC with low levels of MSI (MSI-L) exists; however, its molecular basis is unclear. There is another type of MSIelevated microsatellite alterations at selected tetranucleotide repeats (EMAST)-where loci containing [AAAG] n or [ATAG] n repeats are unstable. EMAST is frequent i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
234
4
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(256 citation statements)
references
References 37 publications
16
234
4
2
Order By: Relevance
“…HCT116 cells, which are deficient in MLH1 and MSH3, complemented with MLH1 through the addition of chromosome 3 have been shown to demonstrate mononucleotide repeat stability but still a low level of dinucleotide and a high level of tetranucleotide repeat instability suggesting a problem in MSH3. Although, the tetranucleotide repeat markers represented a level of instability five times higher than dinucleotide repeats supporting the functional overlap of MutSb and MutSa in IDL2 repair, low dinucleotide repeat instability was caused by defected MutSb (MSH3) (Haugen et al, 2008). The microsatellite stability was indeed reversible by complementing HCT116 cells with both chromosomes 3 and 5, hence expressing both lost proteins MLH1 and MSH3 (Haugen et al, 2008).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…HCT116 cells, which are deficient in MLH1 and MSH3, complemented with MLH1 through the addition of chromosome 3 have been shown to demonstrate mononucleotide repeat stability but still a low level of dinucleotide and a high level of tetranucleotide repeat instability suggesting a problem in MSH3. Although, the tetranucleotide repeat markers represented a level of instability five times higher than dinucleotide repeats supporting the functional overlap of MutSb and MutSa in IDL2 repair, low dinucleotide repeat instability was caused by defected MutSb (MSH3) (Haugen et al, 2008). The microsatellite stability was indeed reversible by complementing HCT116 cells with both chromosomes 3 and 5, hence expressing both lost proteins MLH1 and MSH3 (Haugen et al, 2008).…”
Section: Discussionmentioning
confidence: 81%
“…However, the degree and type of MSI differ from high to low and between mono-, di-, tri-and tetranucleotide instability or elevated microsatellite alterations at selected tetranucleotide repeats (EMAST) (PeltomĂ€ki and Vasen, 2004;Plaschke et al, 2004;Haugen et al, 2008) depending on the MMR gene affected. MLH1-and MSH2-deficient tumours are characterised by both mono-and dinucleotide repeat instability, whereas the level of MSI is lower in MSH6-deficient tumours (Bhattacharyya et al, 1995;Papadopoulos et al, 1995).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While the etiology of EMAST is still not clear, general clues point toward some epigenetic relaxation of DNA MMR as one possibility for its cause. It has been shown that (a) colon cancers have heterogeneous expression of the DNA MMR protein MSH3, 8 suggesting an acquired loss and (b) oxidative stress has been shown to reduce the expression of MSH6 and PMS2, causing faulty DNA MMR that can be corrected when the stress is removed. 9,28 Additionally, we show in the present study a linkage between EMAST and chronic inflammation, further suggesting that inflammation may fuel the occurrence of EMAST in rectal and possibly other tumors.…”
Section: Discussionmentioning
confidence: 99%
“…8 Although the underlying mechanism behind EMAST remains unknown, the authors suggests that MSH3, an MMR gene involved in repair of longer repeat sequences such as those greater than dinucleotide repeats, may be linked to EMAST due to its "heterogeneous" immunohistochemical expression in some colon cancers. 8 This type of pattern suggests an acquired defect, as no germ line mutation in MSH3 has ever been demonstrated. 2 Some MMR genes, in particular MSH6 and PMS2, can be downregulated in the setting of inflammation, 9 suggesting a potential mechanism for "relaxation" of DNA MMR function.…”
Section: Introductionmentioning
confidence: 99%